Formation of Self-Concept through Interpersonal Communication of Ustadz and Santri at Islamic Boarding Schools in Sidoarjo Regency - Wildan Rizki Ramadan; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine how interpersonal communication between ustadz and students forms self-concept at Al Fattah Gesing Islamic Boarding School Banjarsari Buduran Sidoarjo. The results of this study prove that Ustadz can build effective interpersonal communication with students in inculcating moral values ​​at Al-Fattah Islamic Boarding School because they pay attention to important aspects in interpersonal communication (namely: (1) openness; (2) empathy; (3) support; (4) positive; and (5) equality in the process of moral cultivation. The supports faced by Ustadz can build interpersonal communication with students in inculcating moral values ​​at Al-Fattah Islamic Boarding School are as follows: (1) Communication (in the form of advice, direction, and the like) that Ustadz does does not seem to force the students, so that students don't feel too tense when getting guidance from Ustadz; (2) Ustadz already know the background, personality, and life of students in the boarding school; (3 ) There is good coordination between Ustadz and HISFA (Al Fattah Santri Association) management.